2021
DOI: 10.1136/jmedgenet-2021-107965
|View full text |Cite
|
Sign up to set email alerts
|

Role of genetics in amyotrophic lateral sclerosis: a large cohort study in Chinese mainland population

Abstract: BackgroundA large number of new causative and risk genes for amyotrophic lateral sclerosis (ALS) have been identified mostly in patients of European ancestry. In contrast, we know relatively little regarding the genetics of ALS in other ethnic populations. This study aims to provide a comprehensive analysis of the genetics of ALS in an unprecedented large cohort of Chinese mainland population and correlate with the clinical features of rare variants carriers.MethodsA total of 1587 patients, including 64 famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…In addition, as described in our previous studies [14, 19], demographic data, clinical data, and assessment of motor severity, cognitive function, depression and anxiety were collected. A total of 1866 Chinese controls, including 998 males and 868 females, whose mean age was 57.9 ± 9.0 years and who had neither a medical nor family history of neurodegenerative disorders, were used as the control group in our genetic studies for neurodegenerative diseases [20]. This study was approved by the ethics committee of West China Hospital, Sichuan University.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, as described in our previous studies [14, 19], demographic data, clinical data, and assessment of motor severity, cognitive function, depression and anxiety were collected. A total of 1866 Chinese controls, including 998 males and 868 females, whose mean age was 57.9 ± 9.0 years and who had neither a medical nor family history of neurodegenerative disorders, were used as the control group in our genetic studies for neurodegenerative diseases [20]. This study was approved by the ethics committee of West China Hospital, Sichuan University.…”
Section: Methodsmentioning
confidence: 99%
“…In total, seven rare missense variants in CYLD have been identified in 7 (0.72%) patients among 978 sALS patients, and two (4.3%) rare missense variants were identified among the 46 fALS cases, where familial cases had a relatively higher variation frequency. This phenomenon could be due to the following: firstly, as found in our previous study, familial cases are much more likely be caused by genetic causes than sporadic cases (40.6% in fALS vs. 8.6% in sALS) ( Chen et al, 2021 ); secondly, the sample size of familial cases was relatively small. It is interesting to note that, besides the classical phenotype of ALS and ALS with cognitive impairment, our current study found one familial case presenting with a comorbidity of ALS and PSP who had rapid progression and short survival.…”
Section: Discussionmentioning
confidence: 75%
“…To date, more than 238 SOD1 mutations have been reported ( http://www.hgmd.cf.ac/uk/ ). In our previous research, we found that SOD1 is the most common causative gene, followed by FUS, TARDBP, VCP , and OPTN and that it accounts for 21.88% of fALS in Southwest China ( 15 , 16 ). Analyzing this large family indicated that the patients with ALS carried SOD1 p.H47R variant (also coded as p.H46R), which has been reported to be the most frequent variant in Chinese ALS patients with SOD1 mutations ( 17 ).…”
Section: Discussionmentioning
confidence: 98%